Evaluation on occluded hydrocarbon in deep–ultra deep ancient source rocks and its cracked gas resources - Jian Li; Yifeng Wang; Wei Ma; Dongliang Wang; Chenghua Ma; Zhisheng Li (Natural Gas Industry B, 2015)
Oil-cracked gas, as the main type of high-over mature marine natural gas in China, is mainly derived from occluded hydrocarbon. So it is significant to carry out quantitative study on occluded hydrocarbon. In this paper, the occluded hydrocarbon volume of the main basins in China was calculated depending on their types, abundances and evolution stages by means of the forward method (experimental simulation) and the inversion method (geologic profile dissection). And then, occluded hydrocarbon evolution models were established for five types of source rocks (sapropelic, sapropelic prone hybrid, humic prone hybrid, humic and coal). It is shown that the hydrocarbon expulsion efficiency of sapropelic and sapropelic prone hybrid excellent source rocks is lower than 30% at the low-maturity stage, 30%–60% at the principal oil generation stage, and 50%–80% at the high-maturity stage, which are all about 10% higher than that of humic prone hybrid and humic source rocks at the corresponding stages. The resource distribution and cracked gas expulsion of occluded hydrocarbon since the high-maturity stage of marine source rocks in the Sichuan Basin were preliminarily calculated on the basis of the evolution models. The cracked gas expulsion is 230.4 × 1012 m3 at the high evolution stage of occluded hydrocarbon of the Lower Cambrian Qiongzhusi Fm in this basin, and 12.3 × 1012 m3 from the source rocks of Sinian Doushantuo Fm, indicating good potential for natural gas resources. It is indicated that the favorable areas of occluded hydrocarbon cracked gas in the Qiongzhusi Fm source rocks in the Sichuan Basin include Gaoshiti–Moxi, Ziyang and Weiyuan, covering a favorable area of 4.3 × 104 km2.